Quantification of the content of nitrates, fluorides, sulfates, chlorides, carbonates, hydrogen carbonates, sodium, potassium, rotal salts and total hardness in waters of Santa Rosa (LP) (Semiárida, 2020)
Between the months of August 1985 and May 1986, 83 samples of water from different section of Santa Rosa city were analyzed to know the contens of: de NO3-, F-, SO4 2-, Cl-, CO32-,HCO3-,  Na+, K+, total salt and D.T. in well water destined for human consumption. In the analyzed samples the following vas detected:- 43% of them surpases the acceptable value as regardes F-- The 8,5% of them contains an excess of NO3-- The 35% of them have a high content of SO42-- The 23% of them have surfaces the normal values of Cl-- Only 22% of them take tolerable contains of T.H., total salt and other studied ions.
Keywords: water